Delayed Local Recurrence Following Radiation Therapy for Muscle-Invasive Bladder Cancer Emphasizing the Need for Lifelong Surveillance: a Case Report - Rajitha Sunkara; Rajinikanth Ayyathurai; Alan Nieder; Murugesan Manoharan (The Scientific World Journal)
We report a case of 68-years-old gentleman who developed a delayed local recurrence, 30 years following curative radiation treatment for muscle-invasive bladder cancer. This case emphasizes the importance of lifelong post-treatment surveillance for bladder cancer.